Quantitative imaging of Caenorhabditis elegans dauer larvae during cryptobiotic transition - Kim, Kyoohyun; Gade, Vamshidhar R; Kurzchalia, Teymuras V; Guck, Jochen (Biophysical journal, 2022)
Upon starvation or overcrowding, the nematode Caenorhabditis elegans enters diapause by forming a dauer larva, which can then further survive harsh desiccation in an anhydrobiotic state. We have previously identified the genetic and biochemical pathways essential for survival-but without detailed knowledge of their material properties, the mechanistic understanding of this intriguing phenomenon remains incomplete. Here we employed optical diffraction tomography (ODT) to quantitatively assess the internal mass density distribution of living larvae in the reproductive and diapause stages. ODT revealed that the properties of the dauer larvae undergo a dramatic transition upon harsh desiccation. Moreover, mutants that are sensitive to desiccation displayed structural abnormalities in the anhydrobiotic stage that could not be observed by conventional microscopy. Our advance opens a door to quantitatively assessing the transitions in material properties and structure necessary to fully understand an organism on the verge of life and death.